2020
DOI: 10.1177/0022146520936208
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Justice Contacts and Psychophysiological Functioning in Early Adulthood: Health Inequality in the Carceral State

Abstract: Despite increased attention to the links between the criminal justice system and health, how criminal justice contacts shape health and contribute to racial health disparities remains to be better understood. Using data from the National Longitudinal Study of Adolescent to Adult Health (N = 5,488) and several analytic techniques—including a quasi-treatment–control design, treatment-weighting procedures, and mediation analyses—this study examines how criminal justice contacts shape inflammatory and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 59 publications
2
42
1
Order By: Relevance
“…The fact that we did not seem to find a health effect of detention is contrary to the findings from existing longitudinal survey-based studies, which did suggest detrimental health effects [ 13 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. These studies showed that incarceration was associated with mental health problems (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The fact that we did not seem to find a health effect of detention is contrary to the findings from existing longitudinal survey-based studies, which did suggest detrimental health effects [ 13 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. These studies showed that incarceration was associated with mental health problems (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, relatively few studies examined the health of female prisoners. To the best of our knowledge, only a dozen studies had a research design that countered these limitations [ 13 , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. These studies, however, were all done in the United States or Australia, and only one used administrative health data instead of survey data, the latter being hampered by recall and social desirability biases.…”
Section: Introductionmentioning
confidence: 99%
“…Racial disparities in arrests and incarceration contribute to disparities in health outcomes caused by racism, with a recent study indicating that a greater number of criminal legal contacts among Black individuals contributes to more depressive symptoms, compared to White individuals. 39 We also must understand how the outcomes of the criminal legal system vary based on the color of the victim. Studies of execution outcomes point to inequity of Black and White lives, as defendants convicted of killing White victims were executed at a rate 17 times greater than those convicted of killing Black victims.…”
Section: Criminal Legalmentioning
confidence: 99%
“…Another line of work developed in the psychoimmunology literatures maintains that incarceration triggers an upregulated, acute stress response that leads to physiological deterioration (Massoglia and Pridemore 2015). Empirical research indeed finds that formerly incarcerated persons have elevated levels of morbidity, especially for stress-related illnesses, and heightened risk for premature mortality (e.g., Boen 2020).…”
mentioning
confidence: 99%
“…Because of the reliance on self-report instruments, the extent to which incarceration exposure becomes biologically embedded or “gets under the skin” is not well understood. Although objective biomarkers have been featured in some studies of incarceration and health, this work remains scarce (e.g., Boen 2020).…”
mentioning
confidence: 99%